Maximizing Project Success Through Human Performance. - Tirado, Bernardo (Berrett-Koehler Publishers, Incorporated, 2013)
Project management is often defined by processes and methodology, but projects are accomplished by people. Successfully leading those people is the core of a project manager's job. Even the seasoned project manager will encounter situations that present unique leadership challenges.Bernardo Tirado offers a clear path to help develop leadership skills within the project management framework. Using a hands-on, practical approach, he presents a model for taking any project manager's leadership skills to the next level. His model focuses on techniques to develop and apply three areas of awareness-